Las formalidades ad luciditatem y ad regularitatem en el contrato de franquicia en Colombia. (2016)
The present study aims to analyze how the contractual control emanated from the franchise agreement is related to some formalities, which are imposed as a rule of public order for the clear benefit of the consumer and the franchisee. For this purpose a notion of control is presented as manifested in Colombian regulations. It describes when the administrative management in a company is controlled and what is the natural control in the franchise is considered. All of the above is aimed at highlighting the importance of the formalities ad luciditatem and ad regularitatem and in order to demonstrate that their non-compliance will harm certain individuals who appear in the chain of franchises.